2011
DOI: 10.1007/s12010-011-9277-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Sequencing, and Identification Using Proteomic Tools of a Protease from Bromelia hieronymi Mez

Abstract: Fruits of Bromelia hieronymi, a tropical South American plant, possess a high content of peptidases with potential biotechnological uses. Total RNA was extracted from unripe fruits and peptidase cDNA was obtained by 3'RACE-PCR. The consensus sequence of the cysteine peptidase cDNA contained 875 bp, the 690 first ones codifying for a hypothetical polypeptide chain of the mature peptidase, named Bh-CP1 (molecular mass 24.773 kDa, pI 8.6, extinction molar coefficient 58,705 M(-1) cm(-1)). Bh-CP1 sequence shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mehaia [ 68 ], for instance, indicated that clotting time of bovine milk can be longer when the concentration ratio of the protein content of the coagulant enzyme is increased because of the increased effectiveness of collisions due to a decreasing aqueous phase. Bruno et al [ 69 ] also reported that a higher dilution of hieroymain fruit extract prolonged bovine milk clotting time. In contrast, a significant decrease in bovine milk clotting time was observed with an increase in the amount of Solanum macrocarpon extract [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mehaia [ 68 ], for instance, indicated that clotting time of bovine milk can be longer when the concentration ratio of the protein content of the coagulant enzyme is increased because of the increased effectiveness of collisions due to a decreasing aqueous phase. Bruno et al [ 69 ] also reported that a higher dilution of hieroymain fruit extract prolonged bovine milk clotting time. In contrast, a significant decrease in bovine milk clotting time was observed with an increase in the amount of Solanum macrocarpon extract [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…B. hieronymi is a species with a proteolytic system that has been previously studied by our work group (Bruno et al 2008(Bruno et al , 2011. Protein extracts from its fruits contain high amounts of cysteine proteases capable of hydrolysing both whey proteins and casein and may be employed as a milk clotting agent (Bruno et al 2010).…”
Section: Proteolytic Extractsmentioning
confidence: 99%
“…Bromelia hieronymi is a native species from Argentina, whose fruits contain high amounts of many cysteine proteases studied and characterised by our research group (Bruno et al 2008(Bruno et al , 2010(Bruno et al , 2011, but not industrially used yet. The objective of the present work was to obtain a partially purified proteolytic extract from unripe fruits of B. hieronymi and to evaluate its suitability for the preparation and characterisation of a bovine whey protein hydrolysate with ACEinhibitory activity, thus adding value to an abundant byproduct of the dairy industry.…”
Section: Introductionmentioning
confidence: 99%